Correlation of blood glucose level in gingival crevicular blood and finger capillary blood using glucometer - Supreet Jain; Mathod C Shashikanth; Jaideep Sur; Fatima Khan; Sheetal Mujoo; Deeplaxmi Dewangan (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Aim: The aim of the study was to assess the reliability of gingival crevicular blood (GCB) glucose level compared with finger capillary blood (FCB) glucose level using a glucose self-monitoring device (Contour ® TS). Materials and Methods: One hundred randomly selected patients with gingivitis (45 subjects) and periodontitis (55 subjects) were included in the study. The mean age of the study group subjects was 35.39 ± 11.97 years (range 17-70 years). The blood glucose values obtained from GCB elicited during routine periodontal probing and those of peripheral finger stick blood glucose were recorded using a glucose self-monitoring device (glucometer) during fasting and postprandial phases. Statistical analysis was done using Student′s "t" test and Karl Pearson′s product moment correlation. The regression analysis was then performed to compare the GCB and FCB blood glucose readings using the approach of Bland and Altman. Results: There was no statistically significant difference (t = 1.443, P = 0.152) between the fasting GCB and FCB glucose values, but it was significant during postprandial measurement (t = 6.893, P < 0.001). Pearson′s correlation showed a positive correlation between the two measurements (r = 0.893, P < 0.001). Bland-Altman regression analysis revealed sufficient agreement between the two values. Conclusion: The results suggest that GCB collected during diagnostic periodontal examination may be an excellent source of blood for glucometric analysis. Thus, it can be used as a chairside investigative procedure.